The impact of exposure to sugary drink marketing on youth brand preference and recall: a cross-sectional and multi-country analysis - Lauren Remedios; Marie-Hélè; Lana Vanderlee; David Hammond; Monique Potvin Kent (BMC, 2024)
Abstract Background Consumption of sugary drinks (SD) among children and adolescents is a prevalent public health issue both within Canada and worldwide. This problem is exacerbated by the powerful marketing of such beverages to youth, which is known to influence a wide range of dietary behaviours. Methods A cross-sectional, secondary analysis of the International Food Policy Survey Youth Wave 2019 was conducted to assess the relationship between self-reported exposure to SD marketing within the past 30 days or SD brand advertisements and brand preference and brand recall among youth aged 10-17 from Australia, Canada, Chile, Mexico, the United Kingdom, and the United States. Ordinal, multinomial, and binary logistic regression were used as appropriate to examine these associations. Results Youth brand preference and recall was positively associated with self-reported exposure to general and brand-specific SD marketing across all countries. No statistical interaction was observed between youth age and SD marketing overall or within countries. Soft drinks, sports drinks, and fruit juice brands were most commonly recalled by all youth. Conclusion Similar results were observed among children and adolescents within all countries. Global marketing policies should consider older children and adolescents to adequately protect and support child health.